A systems biology approach to understanding the function of 5T4 oncofetal glycoprotein in ovarian cancer and the preclinical effectiveness of a 5T4 antibody drug conjugate. (23rd February 2017) - Wan, Y Louise; Stevens, Adam; Hampson, Lynne; Kitchener, Henry; Stern, Peter
Abstract: Background: 5T4 is a tumour-associated antigen whose expression is associated with poor prognosis in ovarian cancer. Its expression is associated with epithelial-mesenchymal transition and modulation of cell movement via Wnt and chemokine pathways. How these pathways integrate to affect metastasis is yet to be fully elucidated. We aimed to use a systems biology approach to identify regulators of the 5T4 phenotype and evaluate the preclinical efficacy of an antibody drug conjugate (ADC) targeting 5T4 cells (5T4-ADC). Methods: 5T4-specific TALEN and CRISPR–Cas9 constructs were used to knock out 5T4 expression in ovarian cancer cells. Gene expression was assessed in isogenic knockout and control lines by microarray (Human Transcriptome Array 2.0 platform, Affymetrix, Santa Clara, CA, USA). 50% inhibitory concentrations (IC50) of 5T4-ADC in knockout and control cells were determined with MTS (Promega, Madison, WI, USA) and Apotox-Glo (Promega) assays. Antitumour activity of the ADC with and without carboplatin was assessed with bioluminescence imaging in SKOV3-luciferase xenografted NSG mice. Findings: Comparison of the transcriptional profiles of 5T4 wild-type versus knockout SKOV3 cells identified the differential expression of 389 annotated genes (cut off p≤0·01). Network modelling of their associated pathways indicated that the epidermal growth factor receptor (EGFR) was a putative higher order regulator affecting 5T4 transcription. In vitro, IC50 was 20 times lower in SKOV3 cells expressing 5T4 when treated with 5T4-ADC than in 5T4 knockout cells. When tested against established wild-type tumours in vivo, there was a therapeutic reduction in tumour load, delayed tumour growth, and significantly increased survival compared with untreated animals (p=0·0005, log-rank test). Combining ADC treatment with carboplatin (25 mg/kg intraperitoneally) increased median survival a further 71% (IQR 142–200 days) compared with 5T4-ADC alone (IQR 88–107 days). Interpretation: Our systems based approach indicates that the metastatic phenotype associated with 5T4 expression might be regulated by the activity of EGFR. The use of EGFR inhibitors in ovarian cancers has thus far shown minimal efficacy. By contrast, our preclinical data strongly support the potential for antibody targeting of drugs to ovarian cancers expressing 5T4, because this is specific, efficacious, and in combination with carboplatin can lead to longlasting regression. Funding: Wellcome Trust.